EVALUASI KONDISI RUMAH SEHAT PASCA RENOVASI PADA PERUMAHAN CITRALAND GAMA CITY MEDAN - Martha Mulia, Endi; Tiurma Leonora Ritonga, Isniar; Marcelianga, Andre; Witopo, Edwin (LPPM ISTP, 2025)
A healthy house is one that can fulfill the need for a healthy and comfortable living environment. This study aims to evaluate renovated houses in the Citraland Gama City residential area in Medan. The method used in this research is a descriptive qualitative approach, by evaluating the post-renovation condition of the houses based on three aspects of healthy housing comfort: lighting, temperature & humidity, and sound. The results of the study show that the renovated houses in Citraland Gama City meet the technical requirements of a healthy home, including adequate lighting, sound control, and thermal comfort. The conclusion of the study indicates that two variables (lighting and sound control) fall into the category of highly suitable for a healthy home, while one variable (thermal comfort) is categorized as suitably meeting the requirements of a healthy home.